Impaired auditory and visual time reproduction in adult patients with attention deficit-hyperactivity disorder. Issue 2 (7th February 2021) - Taş Dölek, Gamze; Tugba Ozel-Kizil, Erguvan; Bastug, Gulbahar; Baran, Zeynel; Colak, Burcin
ABSTRACT: Objective: Although impaired time perception is associated with significant disturbance in the everyday functioning of adult patients with Attention Deficit-Hyperactivity Disorder (ADHD), it is not very well studied. The present study aimed to evaluate both visual and auditory time reproduction (TR) by using eight time intervals in adult ADHD patients compared to healthy controls (HC). Method: Wechsler Adult Intelligence Scale-R (WAIS-R), Adult Attention Deficit-Hyperactivity Disorder Self-Report Scale (ASRS), Wender Utah Rating Scale (WURS), Hyperfocusing Scale (HS), Beck Depression Inventory (BDI) and a 2-back task were administered to participants. In TR tasks, participants reproduced the same duration of the auditory/visual stimulus by pressing a key and absolute discrepancy scores (ADS) were calculated. A 2 (Group) x 2 (Task Modality) x 8 (Time Interval: 500, 1000, 2000, 4000, 6000, 8000, 12000 and 16000 msec) mixed-design ANOVA was performed. Results: All clinical scores of ADHD group were higher than HC (p < .001) while WAIS-R and 2-back performances of the groups were similar. Mixed-design ANOVA yielded significant Group and Time Interval main effects as well as a Group X Time Interval effect (both p < .001). ADHD patients had larger ADS than HC and as time intervals increased, error levels increased. Errors for time intervals >8000 msec were more prominent in patients. For both TR tasks, ASRS-hyperactivity/impulsivity scores were the main predictor of ADS in the linear regression analysis, while ASRS-attention deficit and HS scores were excluded. Conclusion: Results of the present study indicate significant TR impairment in adult ADHD regardless of task modality (visual or auditory), depressive symptoms and working memory performances. Longer time intervals in TR tasks differentiated patients better and TR impairment was associated with hyperactivity/impulsivity. These findings should be replicated in larger samples and underlying neurobiological components of impaired TR need to be examined in future research.